Influence of root canal filling techniques on sealer penetration and gutta percha/sealer ratio: a confocal laser scanning microscopy analysis - Ermis, Fatma Macit; Haznedaroğlu, Faruk (Brazilian Dental Science, 2020)
Objective: The influence of four root canal filling techniques on the penetration of an endodontic sealer into dentinal tubules and the gutta percha/ sealer ratio (GP/SR) in root canals was evaluated using confocal laser scanning microscopy (CLSM). Material and Methods: Roots of the maxillary central incisors (n=40) were prepared with ProTaper Universal files up to file F5 and assigned to five groups: continuous wave condensation, lateral condensation, single cone, Thermafill®, and negative control group. After root canal filling with gutta-percha and AH26, along with the addition of 0.01% fluorescein, the roots were cut into 2-mm slices. Using CLSM, the specimens were transversely sectioned at 3, 6, and 10 mm from the apex. Results: Sealer penetration was deeper and more frequent at 10 mm than at the 6mm and 3mm for all obturation technique. Penetration was not significantly affected by obturation techniques except single master cone tecnique. Single cone technique demonstrated the lowest sealer penetration at all levels. However, sealer thickness was strongly dependent on obturation technique. Termafill® demostrated superior GP ratio followed by continuous wave condensation, lateral condensation and single cone. Conclusion: In conclusion, the single cone technique resulted in lower sealer penetration than the other techniques, which did not differ significantly from each other. However, sealer thickness was strongly dependent on obturation technique. Termafill® demostrated superior GP ratio followed by continuous wave condensation, lateral condensation and single cone.KeywordsObturation techniques; Dentinal tubule penetration; Gutta percha, sealer ratio; Confocal laser scanning microscopy.